Ensino de sociologia e educação etnicorracial - Almeida, Alexandre das Neves Ubiali Araujo [UNESP]; Silva, Eva Aparecida da [UNESP]; Cardoso, Fábio Luiz Lopes (Universidade Estadual Paulista (Unesp), 2015)
This work results from PIBID Sub - Project Social Sciences, FCLAr / UNESP , and seeks to build on and the school methodologies involving teachers and students around a major theme of Social Sciences - race relations - in order to produce knowledge and relationships based on respect and appreciation of differences , especially those of "race" , ethnicity as postulates the Law 10639/2003, mandating the teaching of the history and culture of Africa and african-Brazilian.

Este trabalho resulta do Sub-Projeto PIBID Ciências Sociais, da FCLAr/UNESP, e busca construir na e com a escola metodologias que envolvam docentes e alunos em torno de um dos grandes temas das Ciências Sociais – as relações raciais – de modo a produzir conhecimento e relações baseadas no respeito e na valorização das diferenças, em especial as de “raça”, etnia, tal como postula a Lei 10639/2003, que torna obrigatório o ensino da história e cultura da África e afrobrasileira.
Keywords: Sociology of education; Etnicorracial education; High school; Ensino de sociologia; Educação etnicorracial; Ensino médio